2014
DOI: 10.1007/s00894-014-2116-9
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling and virtual screening for antagonists of protease from yellow head virus

Abstract: Yellow head virus (YHV) is one of the causative agents of shrimp viral disease. The prevention of YHV infection in shrimp has been developed by various methods, but it is still insufficient to protect the mass mortality in shrimp. New approaches for the antiviral drug development for viral infection have been focused on the inhibition of several potent viral enzymes, and thus the YHV protease is one of the interesting targets for developing antiviral drugs according to the pivotal roles of the enzyme in an ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Considering the genetic similarity and mactching residue position of 3CL pro H63 and C152 in the catalytic dyad of both GAV and YHV 3CL pro ( Fig. 1A ), we identified H63 as one of the catalytic residues in our model instead of the previously proposed H30 ( Unajak et al, 2014 ). The designation of H63 as part of the YHV 3CL pro catalytic dyad is in great accordance with the previous experimental reports ( Ziebuhr et al, 2003 ).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Considering the genetic similarity and mactching residue position of 3CL pro H63 and C152 in the catalytic dyad of both GAV and YHV 3CL pro ( Fig. 1A ), we identified H63 as one of the catalytic residues in our model instead of the previously proposed H30 ( Unajak et al, 2014 ). The designation of H63 as part of the YHV 3CL pro catalytic dyad is in great accordance with the previous experimental reports ( Ziebuhr et al, 2003 ).…”
Section: Resultsmentioning
confidence: 83%
“…Thus, the model YHV_M2 was chosen to be a representative model for YHV 3CL pro in the following studies. The previous homology based model of YHV 3CL pro suggested H30, D70, and C152 as 3 catalytic residues that form the catalytic triad of the protease ( Unajak et al, 2014 ). On the contrary, our predicted model from AlphaFold2 indicated that the YHV 3CL pro employs H-C catalytic dyad for proteolytic mechanism which is in good agreement with the previous experimental data obtained from GAV 3CL pro ( Ziebuhr et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations